Comparison of the biochemical and hematological profiles of patients with COVID-19 in their different outcomes: Hospital discharge and death (Research, Society and Development, 2022)
Introduction: The virus that causes COVID-19, SARS-CoV-2, has as its main focus of involvement the respiratory tract, even today with many patients evolving to the most severe form. Therefore, it is necessary to identify early signs and symptoms of COVID-19, as well as possible risk factors and signs of poor prognosis involved in the progression of the disease. Objective: The present study aimed to evaluate biochemical, hematological and coagulation tests in patients diagnosed with COVID-19 in order to identify a prognostic pattern for the outcomes of hospital discharge and death from a descriptive data compilation from a public repository. Methodology: Data from patients seen between February 26 and June 27, 2020 at Hospital Sírio-Libanês, made available by a public repository, were divided into two categories for analyses. Demographic data (gender, age and city where the patient resides) and clinical/laboratory data (test results) were analyzed, including the outcome (discharge or death). Results: Older age and male gender were more associated with the outcome of death. D-dimer and blood glucose were higher in the death group, while GFR worsened in both groups and APTT, total bilirubin, serum creatinine, blood glucose, D-dimer and CRP increased in the outcome only of patients who died, the latter reduced in the "hospital discharge" group. Moreover, there were lower rates of hemoglobin, erythrocytes and hematocrit, platelets and lymphocytes, as well as increased leukocytes, neutrophils and basophils in the group of patients who died. Conclusion: The variations found in biochemical parameters suggest especially that hyperglycemia is associated with more severe cases, while the analysis of inflammation confirms by CRP that this condition was more exacerbated in patients who died. In coagulation analysis, increased D-dimer was associated with more severe cases, and in hematology, the results reflect a higher risk of anemia and systemic inflammatory response.